Study of Neuropilin-1/Cd304 Expression in Leukemogenesis - Radwan, Shabaan; A. Allam, Ahmed; P. Aziz, Shereen; Mostafa Ali, Elsayed; Ragab, Mostafa (Journal of Hematology and Oncology Research, 2018)
Neuropilins are transmembrane glycoproteins that act as receptors for vascular endothelial growth factors (VEGF) and are involved in the process of tumor angiogenesis. Its importance in hematological malignancies such as acute leukemia (AL) remains to be elucidated. The aim of this study was to evaluate the significance of neuropilin-1 expression in acute myeloid leukemia (AML) and acute lymphocytic leukemia (ALL) patients by flowcytometry and the difference between both groups of acute leukemia. Bone marrow aspirates of 52 patients with acute leukemia, 29 patients with de novo AML and 23 ALL patients were examined in this study. 15 subjects with non-hematological malignancy serving as the control group were also included. Neuropilin-1 expression by flow cytometry showed a highly significant increase in de novo AML and ALL patients with a mean of 37.9 ± 20.92% and 32.33±19.8%, respectively, compared to control group’s mean of 11.51 ± 3.04% (p= 0.001, 0.006). There were no statistically significanct difference between ALL and AML patients (p= 0.76). Neuropilin-1 surface expression by flowcytometry showed a significant positive correlation with total leukocyte count, bone marrow blast percentage, CD45 and CD14 and negative correlation with hemoglobin level, RBCs count in AML patients. In ALL patients, positive significant correlations were found with bone marrow blast percentage and negative correlation with hemoglobin level, RBCs count. Neuropilin-1expression was detected significantly in acute leukemias and it is related to the disease severity.
Keywords: Neuropilin-1; Acute myeloid leukemia; Acute lympohoid leukemia.